2018
DOI: 10.1038/s41598-018-28412-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving of hydrolases biosythesis by solid-state fermentation of Penicillium camemberti on rapeseed cake

Abstract: The study show usefulness of rapeseed cake, rich in fats and proteins byproduct generated after oil production, which may be used as a microbial medium for lipase and protease biosynthesis. Of 26 different filamentous fungi screened by solid-state fermentation, Penicillium camemberti AM83 was found to abundantly produce lipase and protease. Various process parameters were then optimized to maximize lipase and protease secretion, including carbon and nitrogen source, C/N ratio, metal ions, temperature, moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
(69 reference statements)
0
20
1
1
Order By: Relevance
“…This had also a positive effect on the dry weight of the mycelial biomass obtained on all three media (Table 2). Some studies have described a positive effect of Ca 2+ ions increasing the biosynthesis of lipases, e.g., lipases from Bacillus cereus [44] and Penicillium camemberti [45]. However, in this study, the increase in lipase biosynthesis by C. pannorum A-1 does not seem to be caused directly by Ca 2+ ions, because there were no significant differences in the activities between the BMC and BM media (without olive oil and glucose).…”
Section: Discussioncontrasting
confidence: 74%
“…This had also a positive effect on the dry weight of the mycelial biomass obtained on all three media (Table 2). Some studies have described a positive effect of Ca 2+ ions increasing the biosynthesis of lipases, e.g., lipases from Bacillus cereus [44] and Penicillium camemberti [45]. However, in this study, the increase in lipase biosynthesis by C. pannorum A-1 does not seem to be caused directly by Ca 2+ ions, because there were no significant differences in the activities between the BMC and BM media (without olive oil and glucose).…”
Section: Discussioncontrasting
confidence: 74%
“…This further proved that B. amyloliquefaciens CX-20 could produce many enzymes to hydrolyze the carbohydrates of RSC into reducing sugars. It has been reported that rapeseed oil could be used as a source of carbon to ferment microbial products such as lipase [23], erythromycin [30] and isocitric acid [31]. However, whether the residual oil in RSC could be used as a carbon source for iturin A production by B. amyloliquefaciens CX-20 was still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…However, unlike carbohydrases and proteases [16], lipases have not been widely used for the pretreatment of rapeseed by-products to improve their value for microbial production. It has been reported that RSC could be used as a valuable raw material for producing lipases and proteases due to its high content of lipids and proteins [23]. Therefore, it seems feasible to use lipases to solve the problem of high oil content in RSC.…”
Section: Introductionmentioning
confidence: 99%
“…RSM is a good protein source for the microbial fermentation of high‐value‐added products (Wang et al ., 2010; Kiran et al ., 2013; Chatzifragkou et al ., 2014; Jaszek et al ., 2016; Prendecka et al ., 2016; Boratyński et al ., 2018), but its particular physical and chemical structure limited the nutrients to be directly assimilated by the majority of industrial microorganisms without pretreatment (Wang et al ., 2010). Consequently, the application of RSM hydrolysate produced following fungal pretreatment as a feedstock for microbial bioconversions has been intensively investigated (Wang et al ., 2010; Kiran et al, 2012, 2013; García et al ., 2013; Chatzifragkou et al ., 2014; Salakkam et al ., 2017; Salakkam and Webb, 2018).…”
Section: Discussionmentioning
confidence: 99%